The Model of Teachers Communication Based on Multicultural Values in Rural Early Childhood Education - Dakir Dakir; Akmal Mundiri; Muhammad Ainul Yaqin; Niwati Niwati; Ida Subaida (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
The phenomenon of the absence of moral decadence and appropriate behavior such as violence, brawls, exclusivism, and a lack of tolerance and respect for others in all forms involving students is an ineffective model of education and function. The dysfunction is caused by not conveying the message desired by the teacher. Thus, this study aimed to describe the multicultural values-based teacher communication model in early childhood education institutions in rural areas. This research used a case study approach. This study indicates that the multicultural value-based teacher communication model in early childhood education institutions in rural areas is carried out in the form of verbal and non-verbal communication. In verbal communication, messages are conveyed verbally and in writing. Meanwhile, in the non-verbal communication process, the messages conveyed are in the form of persuasive power, coercive and reward power, personal imitation, and educative interactions vertically and horizontally